Design, synthesis and biological evaluation of (E)-3, 4-dihydroxystyryl 4-acylaminophenethyl sulfone, sulfoxide derivatives as dual inhibitors of HIV-1 CCR5 and integrase. Issue 3 (1st February 2017) - Sun, Yixing; Xu, Weisi; Fan, Ningning; Sun, Xuefeng; Ning, Xianling; Ma, Liying; Liu, Junyi; Wang, Xiaowei
Graphical abstract: Abstract: Aiming at the limited effectiveness of current clinical therapeutic effect of AIDS, novel series of compounds bearing ( E )-3, 4-dihydroxystyryl sulfone (or sulfoxide) and anilide fragments were designed and synthesized as dual inhibitors of HIV-1 CCR5/IN. The biological results indicated that several target compounds showed inhibitory activity against HIV-1 Bal (R5) infection in TZM-bl cells. Besides targeting the chemokine receptor on the host cell surface, they also displayed binding affinities with HIV-1 integrase using the surface plasmon resonance (SPR) binding assays. Molecular docking studies have inferred the possible binding mode of target compounds against integrase. These data demonstrate that the structure of ( E )-3, 4-dihydroxystyryl sulfone and sulfoxide derivatives have the potential to derive potent dual inhibitors of HIV-1 Integrase and CCR5.